America, the Vietnam War, and the world : comparative and international perspectives - Daum, Andreas W.; Gardner, Lloyd C., 1934-; Mausbach, Wilfried, 1964- (Washington, D.C. : German Historical Institute ; New York : Cambridge University Press, 2003)
This book presents new perspectives on the Vietnam War, its global repercussions, and the role of this war in modern history. The volume revels "America's War" as an international event that reverberated all over the world: in domestic settings of numerous nation-states, combatants and noncombatants alike, as well as in transnational relations and alliance systems. The volume thereby covers a wide geographical range - from Berkely and Berlinto Cambodia and Canberra. [In the book], 'America's War' is thus depicted as a truly global event whose origins and characteristics deserve an interdisciplinary treatment.
Introduction: America's war and the world Andreas W. Daum, Lloyd C. Gardner and Wilfried Mausbach; Part I. Relocating Vietnam: Comparisons in Time and Space: 1. A colonial war in a postcolonial age: the United States's occupation of Vietnam Michael Adas; 2. Visions of the Asian periphery: Vietnam (1964-8) and the Philippines (1898-1900) Fabian Hilfrich; 3. The challenge of revolutions and the emergence of nation-states: British reactions to the foundation of the United States and American responses to the Socialist Republic of Vietnam, 1780-1980 T. Christopher Jespersen; 4. A comparative study of peripheral wars: the United States in Vietnam and Japan in China John Prados; 5. The Panmunjom and Paris armistices: patterns of war termination Jeffrey Kimball; 6. Versailles and Vietnam: coming to terms with war Sabine Behrenbeck; Part II. International Relations and the Dynamics of Alliance Politics: 7. Who paid for America's war? Vietnam and the international monetary system, 1960-75 Hubert Zimmerman; 8. America isolated: the western powers and the escalation of the war Fredrick Logevall; 9. Bamboo in the shadows: United States relations with Thailand during the Vietnam war Arne Kislenko; 10. The strategic concerns of a regional power: Australia's involvement in the Vietnam war Peter Edwards; 11. 'Peoples' warfare versus peaceful coexistence?' Vietnam and the Sino-Soviet struggle for ideological supremacy Eva-Maria Stolberg; Part III. Recasting Vietnam: Domestic Scenes and Discourses: 12. The center-left government in Italy and the escalation of the Vietnam war Leopoldo Nuti; 13. Auschwitz and Vietnam: West German protest against America's war during the 1960s Wilfried Mausbach; 14. The world peace council and the antiwar movement in east Germany Gunter Wernicke; 15. All power to the imagination! Antiwar activism and emerging feminism in the late 1960s Barbara Tischler; 16. Vietnam: many wars? Lloyd C. Gardner; Index.
Includes bibliographical references and index.
ENH
Trim Education
Keywords: Vietnam War, 1961-1975.; Vietnam War, 1961-1975 -- United States; World politics -- 20th century; English language